Performance and Maximum Functional Masticatory Force in Patients with Dentomucosal-supported and Implant-supported Removable Partial Dentures - Mauricio Toro; Alain Manuel Chaple-Gil; Fernando Romo; Leonardo Díaz (Editorial Ciencias Médicas, 2024)
Introduction: Due to edentulousness, masticatory performance and masticatory force decrease, which implies a disorganization and decompensation of the stomatognathic system with forces provoked by mastication, which are distributed in the bone through teeth and mucous membranes and cause bone resorption in edentulous areas. Objective: To compare masticatory performance and maximum functional masticatory force in partially edentulous patients with dentomucosally supported removable partial dentures before and after surgical installation of osseointegrated implants as auxiliary prosthetic abutments. Methods: Ten patients rehabilitated with removable partial dentures were selected. The biomechanical test of masticatory force measurement and the Manly test were performed to evaluate masticatory performance before implant installation and at three- and six-months post-surgery. Results: An average masticatory performance value of 24.2 ± 9.73 % was obtained before implant surgery, 44.1 ± 13.28 % at three months and 45.6 ± 14.33 % at six months after implant surgery (p = 0.001). Before implant surgery, an average masticatory force of 10.6 ± 4.34 kg, 12.5  4.28 kg at three months and 15.1 ± 5.12 kg at six months after implant surgery was obtained (p = 0.008). Conclusions: The use of osseointegrated implants as auxiliary abutments in dentomucosally supported removable prostheses are associated with increased masticatory performance and increased maximum functional masticatory force, associated with relief of direct load on edentulous maxillary ridges.